Rats, plague, and religion. - Carman, John Spencer (Philadelphia Judson Press, 1936)
stories of medical mission work in India
Rats, plague, and religion; stories of medical mission work in India
Keywords: Missions -- India. Missions, Medical. Missionary stories. Religious Missions. Medical Missions, Official. Plague. India. Missions